2021
DOI: 10.1016/j.ehpc.2021.200524
|View full text |Cite
|
Sign up to set email alerts
|

Full autopsy in a confirmed COVID-19 patient in Lagos, Nigeria – A case report

Abstract: Objectives To report the postmortem findings of a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) positive individual who died in Lagos (Nigeria) in June 2020 and to investigate the cause, pathogenesis as well as pathological changes noticed during the examination. Methods Complete postmortem examination was performed according to standard procedures in a regular autopsy suite using personal protective equipment including N95 masks, goggles and disposable g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
3
2
Order By: Relevance
“…Autopsy findings of COVID‐19 have been reported from worldwide countries, including the United States, 13 and those from Europe, 14 , 15 , 16 Asia, 12 , 17 , 18 and Africa. 19 No national differences have been described, and most reports stated that DAD is a major cause of respiratory failure, which is different from the present case.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Autopsy findings of COVID‐19 have been reported from worldwide countries, including the United States, 13 and those from Europe, 14 , 15 , 16 Asia, 12 , 17 , 18 and Africa. 19 No national differences have been described, and most reports stated that DAD is a major cause of respiratory failure, which is different from the present case.…”
Section: Discussioncontrasting
confidence: 74%
“…Autopsy findings of COVID-19 have been reported from worldwide countries, including the United States, 13 and those from Europe, [14][15][16] Asia, 12,17,18 and Africa. 19 No national differences have been described, and most reports stated that DAD is a major cause of respiratory failure, which is different from the present case. Since this pandemic occurred, efforts have been made to overcome the exaggerated host immune reactions, and a living WHO guideline on drugs for COVID-19, for example, was repeatedly updated.…”
Section: Discussioncontrasting
confidence: 74%
“…This is an indication that in addition to worsening health situation due to COVID-19 and inability to pay for medication, such families may also experience food insecurity, hunger and deprivation. Previous works have earlier reached similar conclusions that the COVID-19 pandemic has affected various dimensions of food security and households' incomes in developing countries, including in the low income households in high-income-economies like the US [36][37][38]. Furthermore, Olwande et al [39], have shown that the COVID pandemic caused significant decline in households' incomes and negative social and economic impacts on households living in both the urban and rural areas of Kenya.…”
Section: Discussionmentioning
confidence: 71%
“…In the USA, the median charge amount for hospitalization of a COVID-19 patient over a course of treatment until discharged range from US$34,662 for the 23-30 age group to US$45,683 for the 51-60 age group [36,37]. Although no peer-reviewed document exists yet to estimate the cost of hospitalization for a COVID patient in Nigeria, anecdotal estimation placed the average costs at between US$750 to US$13, 000 per person, depending on the duration of hospitalization [38]. These observations have some implications; there may be some distortion of the national epidemiological (morbi-mortality) data, and related health costs on COVID-19 in Nigeria, because individuals in the low and middle income groups would most likely shun hospitalization and post mortem examinations to determine the cause of death largely due to the associated huge costs [39].…”
Section: Discussionmentioning
confidence: 99%
“…A case report in [ 14 ] emphasized the importance of full autopsy in understanding the disease process and identifying potential targets for therapeutic interventions. The authors of the aforementioned study conducted a full autopsy on a confirmed COVID-19 patient in Lagos, Nigeria, providing valuable insights into the pathological features of the disease.…”
Section: Introductionmentioning
confidence: 99%